PENGARUH PEMBERIAN BISKUIT TEMPE TERHADAP PENINGKATAN BERAT BADAN DAN TINGGI BADAN PADA BALITA - Sarmana - -; Rostiodertina - Girsang; Alprindo - Sembiring; Mutiara Dwi Yanti (Program Studi Pendidikan Biologi, 2021)
Nutritional problems in children under five are a fairly large problem and must receive priority treatment. Nutritional problems that often occur are undernutrition and malnutrition. With this problem, it will hamper the increase in human resources where this situation results in growth and development failure and increases mortality and morbidity rates. The purpose of this study was to analyze the effect of giving tempeh biscuits to increase in body weight and height in toddlers at UPT Puskesmas Deli Tua. The research design used was a quasi-experimental approach with a one group pre-post test approach. The population in this study were all children under five who were in the working area of the UPT Puskesmas Deli Tua with a total sample of 96 people. Data were analyzed using Paired t-test. The results showed that the average height before the intervention was 104.31cm and after the intervention was 105.05 cm for the average height before the intervention was 17.25kg and after the intervention was 17.64 kg. Based on the results of bivariate analysis, it was found that there was an effect of giving biscuits to changes in height with a p-value of 0.01 and weight in toddlers with a p-value of 0.0001. It is hoped that health workers will provide counseling to increase the growth of toddlers to prevent undernutrition status.